Faktor-Faktor Yang Berhubungan Dengan Pneumonia Pada Balita Di Wilayah Kerja Puskesmas Rambah Samo 1 Tahun 2014 - Aldriana, Nana (Jurnal Martenity and Neonatal, 2015)
Pneumonia is an acute respiratory infection, which attacks the lung tissue that is characterized by cough accompanied by rapid breathing or shortness of breath. According to the WHO report, about 800,000 to 1 million children die each year because pneumonia. WHO and UNICEF mention pneumonia as the cause of death of children under five. In Riau Province incidence of pneumonia in 2012 amounted to15.9% increase compared to the year 2011 amounted to 13.7% with the number of cases found as many as 10,059 cases. In Rokan Hulu found 2.12% of the number ofcases was 131 cases with the most of cases found in Puskesmas Rambah Samo I (31 cases). The aim of research to determine the factors associated with the occurrenceof pneumonia in children under five in Puskesmas Rambah Samo 1. This type of research is quantitative analytic with case-control design. Total sample of 62 people chosen by using two techniques, namely sampling saturated and simple random sampling. Data analysis was performed using univariate and bivariate with chi square test with a degree of confidence (CI) 95%. Exclusive Asi factor results obtained p value = 0.0001, Immunization Status p value = 0.0001, birth weight p value = 0.05, Age Toddler p value = 0.002 and education p value = 0.006 mother. The conclusion of this study indicate that there is a significant relationship betweenAsi Exclusive, immunization status, birth weight, age and education toddler's mother with pneumonia in the PHC Work Rambah Samo 1 2014. Advice to local health workers are expected to further improve its performance to the public could be more active again in maintaining and improving their health and participate in all programs created by local health workers.